Smart technologies for sustainable smallholder agriculture : upscaling in developing countries - Chikoye, David; Gondwe, Therese; Nhamo, Nhamo (Academic Press, 2017)
Smart Technologies for Sustainable Smallholder Agriculture: Upscaling in Developing Countries defines integrated climate smart agricultural technologies (ICSAT) as a suite of interconnected techniques and practices that enhance quantity and quality of agricultural products with minimum impact on the environment. These ICSAT are centered on three main pillars, increased production and income, adaptation and resilience to climate change, and minimizing GHG emissions. This book brings together technologies contributing to the three pillars, explains the context in which they can be scaled up, and identifies research and development gaps as areas requiring further investigation. It stresses the urgency in critically analyzing and recommending ICSAT and scaling out the efforts of both developing and disseminating these in an integrated manner. The book discusses, synthesizes, and offers alternative solutions to agriculture production systems and socio-economic development. It brings together biophysical and socioeconomic disciplines in evaluating suitable ICSAT in an effort to help reduce poverty and food insecurity.